Radical territories in the Brazilian Amazon : the Kayapó's fight for just livelihoods - Zanotti, Laura (Native peoples of the Americas., 2016)
Radical territories in the Brazilian Amazon sheds light on the creative and groundbreaking efforts Kayapó peoples deploy to protect their lands and livelihoods in Brazil.